"Virtual Pole" method applied at the profiling of the rotary cutter tool for processing of ball screw. Issue 1 (September 2020) - Costin, G A; Teodor, V G; Oancea, N
Abstract: "Virtual pole" method represents a variant of the normals theorem, which can be used for profiling of tools that generate by enwrapping, by the rolling method. This variant of determining the enveloping condition allows to avoid the need to write, in explicit form, the relative movements between the piece and the tool, while remaining scientifically rigorous. In the paper, an application of the „virtual pole" method is presented, for the profiling of the rotary cutter tool designed to process a ball screw type piece. The specific form of the enwrapping condition was compared with a specific form obtained by a classical theorem.